THE EFFECTIVENESS OF SCHOOLOGY ON TECHNOLOGY SKILLS: E-LEARNING INTEGRATION IN EDUCATION - Rully Putri Nirmala Puji; Desi Priyanti (Journal Publicuho, 2021)
Schoology is an e-learning platform that offers several exciting features that can be optimized by educators and students in tandem with parents. This can be one of the media in optimizing strong communication between the three. Schoology is also able to be one of the pathways to improving the skills in utilizing the technology of students who have also become one of the demands of the 4.0 revolution. Schoology is able to be used by educators in particular types of education and in certain subjects. This study aims to identify the effectiveness of Schoology on the technology skills of students in higher education ranking. The research results have shown that Schoology poses an effect on improving technology skills in aspects of text formatting and searching the web.